Land access and feeding strategies in post-Soviet livestock husbandry: Evidence from a rangeland system in Kazakhstan - Robinson, Sarah; Petrick, Martin; Justus Liebig University Giessen (My University, 2024)
Context: Feeding strategy is a major dimension of intensification and largely determines the environmental and economic impacts of livestock production systems, in particular concerning land use competition, greenhouse gas emissions and rural livelihoods. Literature suggests that a key driver of intensification is increasing population density – associated with decreased labor costs, shifts in demand and institutional and political change; whilst at the household level farmer education and market access are also important. However, the topic has not been addressed in the rangelands of post-Soviet Eurasia, where vast underused pasture resources may be reclaimed, but improved feeding is also a key aim of agricultural policy. Objectives: We aim to firstly describe the extent to which land users in an extensive rangeland system in Kazakhstan exploit pastures, arable land or markets to feed their animals, and secondly to explore the determinants of these decisions. Methods: We identify three potential strategies: self-production of roughage or concentrate, purchase of these inputs, or expansion of pasture use through mobile pastoralism. We then investigate the determinants of these feeding strategies and their interactions, including variables capturing farm and farmer characteristics, access to land and other assets and outcomes of post-independence reforms. We examine the factors determining the three feeding strategies using a farm survey dataset from south-eastern Kazakhstan to estimate a simultaneous equation system, considering herd size as an endogenous variable. Results and Conclusions: Herd size combined with access to land for fodder production largely determines how producers feed their livestock. Barriers to the substitution of pasture for purchased or self-produced fodder include cropland access, distance from markets, and credit availability, so that use of remote and seasonal pastures is the major feeding strategy employed by larger producers. Access to both arable land and pasture is dependent on land reform outcomes, which constrain farmers' livestock feeding decisions today. Other factors such as farmer education, human population density and household labor are less important. Significance: Grazing expansion strategies employed by farmers studied here differ from those based on external input use observed in many regions of the world. Instead, they reflect the continuing importance of pastoral resources in rangeland environments implying important trade-offs to intensification which merit further study.
Keywords: ddc:630